2017
DOI: 10.3856/vol45-issue2-fulltext-20
|View full text |Cite
|
Sign up to set email alerts
|

Use of otolith microchemistry as habitat indicator of Anchoa tricolor (Spix and Agassiz, 1829) in a subtropical estuary

Abstract: ABSTRACT. The objective of the present study was to evaluate the use of sagitta otolith microchemistry (Sr:Ca, Ba:Ca ratios) as habitat indicator of Anchoa tricolor between the estuary and the adjacent continental shelf. We analyzed 162 specimens of A. tricolor in the Paranaguá Estuarine Complex (Brazil), and salinity and rainfall data. The biological and environmental data were grouped into sectors (internal, intermediate, and external) and periods (early and late wet, and dry periods). The concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
2
1
0
Order By: Relevance
“…However, the majority of individuals displayed Ba:Ca peaks at both Sr:Ca marine and estuarine levels, consistent with the influence of both factors on Ba absorption into otoliths (Figure 4). These results have shown that, although individual Ba:Ca profiles would not be sufficient to infer C. lucerna movements between different habitat salinities, the combination of their analysis with the Sr:Ca profiles showed to be consistent with the results obtained by other authors on the influence of other factors than salinity in Ba incorporation into otoliths, in particular upwelling processes and freshwater discharges [71,72,75].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, the majority of individuals displayed Ba:Ca peaks at both Sr:Ca marine and estuarine levels, consistent with the influence of both factors on Ba absorption into otoliths (Figure 4). These results have shown that, although individual Ba:Ca profiles would not be sufficient to infer C. lucerna movements between different habitat salinities, the combination of their analysis with the Sr:Ca profiles showed to be consistent with the results obtained by other authors on the influence of other factors than salinity in Ba incorporation into otoliths, in particular upwelling processes and freshwater discharges [71,72,75].…”
Section: Discussionsupporting
confidence: 87%
“…The overall behavior of all Ba:Ca profiles did not reflect an inverse relationship with Sr:Ca ratios and salinity, as described by other authors [30,32,69]. However, several studies have also shown that Ba incorporation into otoliths can be affected by factors such as upwelling phenomena [70][71][72] and terrestrial freshwater contributions (river runoff, groundwater inputs) [73][74][75]. The vast majority (97%) of C. lucerna individuals exhibited variations and peaks in Ba:Ca ratios in the natal region of otoliths that seem to corroborate these findings.…”
Section: Discussionsupporting
confidence: 54%
“…By tracking changes in elemental concentrations over time in an individual fish or among fish captured from different locations, it is often possible to deduce much about their environmental history, such as the previous habitat uses, stock compositions, and nursery locations (Thresher, 1999;Brazner et al, 2004;Avigliano et al, 2018b;Soeth et al, 2019). In recent years, otolith chemical composition has been applied to the study of small pelagic (Mai et al, 2014;Carvalho et al, 2017) and demersal (Volpedo and Fernández Cirelli, 2006;Albuquerque et al, 2012;Avigliano et al, 2017a) fish in the southwestern Atlantic Ocean. Moreover, this technique resolved the population structure of some notothenioid species, such as the Patagonian toothfish Dissostichus eleginoides (Smitt, 1898) (Ashford et al, 2005(Ashford et al, , 2006, and the Scotia Sea icefish Chaenocephalus aceratus (Lönnberg, 1906) (Ashford et al, 2010) successfully.…”
Section: Introductionmentioning
confidence: 99%